The guardians - Grisham, John (2019)
In a small Florida town, a young lawyer, Keith Russo, is shot to death as he works late. A young black man, a former client, named Quincy Miller is charged and convicted. For 22 years, Miller maintains his innocence from inside prison. Finally, Guardian Ministries takes on Miller's case, but Cullen Post, the Episcopal minister in charge, gets more than he bargained for. Powerful people murdered Russo-- they do not want Miller exonerated, and will kill again without a second thought. -- adapted from info provided and jacket info
Keywords: False imprisonment -- Fiction; Murder -- Investigation -- Fiction; Priests -- Fiction; Justice -- Fiction; African Americans -- Fiction; Race relations -- Fiction; Legal stories; Florida -- Fiction; Suspense fiction; Legal stories; Legal fiction (Literature); Thrillers (Fiction); Novels